2021
DOI: 10.3389/fevo.2021.674779
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Change in Locomotion Close to the Origin of Amniotes Inferred From Trackway Data in an Ancestral State Reconstruction Approach

Abstract: Among amniote and non-amniote tetrapod trackways from late Carboniferous to early Permian deposits, certain trackway measures vary notably. Some of this variability can be attributed to evolutionary changes in trackmaker anatomy and locomotion style close to the origin of amniotes. Here we demonstrate that steps in early amniote locomotion evolution can be addressed by applying methods of ancestral state reconstruction on trackway data – a novel approach in tetrapod ichnology. Based on (a) measurements of 186 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Some evidence suggests that the tendency to primarily increase speed through stride frequency may be attributable to the conserved nature of locomotor motor patterns (Buchwitz et al, 2021;Cuff et al, 2019;Goslow et al, 1989;Lauder and Shaffer, 1988;Peters and Goslow, 1983;Wainwright et al, 1989). Utilizing a salamander model, Ijspeert and colleagues (2006Ijspeert and colleagues ( , 2007Ijspeert and colleagues ( , 2008 demonstrated that spinal stimulation of increasing intensity results in frequency-related changes in axial and appendicular movements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence suggests that the tendency to primarily increase speed through stride frequency may be attributable to the conserved nature of locomotor motor patterns (Buchwitz et al, 2021;Cuff et al, 2019;Goslow et al, 1989;Lauder and Shaffer, 1988;Peters and Goslow, 1983;Wainwright et al, 1989). Utilizing a salamander model, Ijspeert and colleagues (2006Ijspeert and colleagues ( , 2007Ijspeert and colleagues ( , 2008 demonstrated that spinal stimulation of increasing intensity results in frequency-related changes in axial and appendicular movements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Granatosky et al (2019a) show that while limb joint kinematics are highly labile across evolutionary history, much of the diversity in limb kinematics is a recent, suggesting mammalian, innovation. Finally, utilizing trackway evidence, Buchwitz et al (2021), proposed that temnospondyls (extinct primitive amphibians) showed little ability to modulate stride length. Such capabilities do not appear in the ichnofossil record until the emergence of Cotylosauria (Amniota+Didectomorpha).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to interpret gaits from fossil trackways remain speculative or inconclusive. 3,4 Stevens et al 5 demonstrated that trackmakers that only slightly differ in body length but employ different limb phases may produce identical footfall patterns. Given this ambiguity, it seemed that limb phase could not be estimated from trackways unless body size and shape of the trackmaker can be precisely constrained 5 -a task that is notoriously difficult to achieve when the assumed trackmaker taxon is extinct.…”
Section: Ambiguity and Within-trackway Variationmentioning
confidence: 99%
“…319 Ma ago; Ford and Benson, 2020). In contrast to the majority of coeval limbed vertebrates, the earliest amniotes and their closest extinct relatives adopted a predominantly or even exclusively terrestrial lifestyle (Sumida, 1997;Nyakatura et al, 2019;Buchwitz et al, 2021). This ecological shift had been accomplished by innovations in their developmental strategies (e.g., Packard and Seymour, 1997;Werneburg, 2019;Blackburn and Stewart, 2021) and was accompanied by further changes in their general anatomy, involving the appendicular skeleton and vertebral column (Sumida, 1997), as well as the skull (Bramble and Wake, 1985;Iordansky, 1990).…”
Section: Introductionmentioning
confidence: 99%